Artificial Corn-Based Diet for Rearing Spodoptera frugiperda (Lepidoptera: Noctuidae). Issue 4 (1st July 2019) - Pinto, José Ricardo Lima; Torres, Aline Finotti; Truzi, Caio Cesar; Vieira, Natalia Fernanda; Vacari, Alessandra Marieli; De Bortoli, Sergio Antonio
Abstract: Spodoptera frugiperda (J.E. Smith, 1797) is considered a key pest of maize. However, the artificial diets used for rearing this insect in the laboratory do not contain corn. The aim of this study was to evaluate the biology and to compare the food consumption by S. frugiperda, as well as the food preference of the larvae in the standard diet and the corn-based diet. Three of the following diets were evaluated: a standard diet based on beans (D1 ), a diet with corn flour as substitute for wheat germ (D2 ), and a diet replacing beans with green corn (D3 ). The biological parameters evaluated were period and survival of larvae and pupae; weight of male and female pupae; sex ratio; fecundity; egg incubation period; and adult longevity. The nutritional indices were determined and the biological data obtained were used to determine the parameters of fertility life tables; we also performed a multiple-choice test (feeding test). Larval development of S. frugiperda occurred in all three diets, although without oviposition by females developed from larval fed on D2 . There was no difference among the diets in relation to the fertility life table parameters. The diet D2 resulted in better ingestion, digestion, assimilation, and conversion of food, but was associated with a metabolic cost to assimilate the food. Using a multiple-choice test, we observed that the larvae preferred diet D2 . Based on our results, the most adequate diets for rearing S. frugiperda in the laboratory are D1 and D3 .